Cost-effectiveness comparison between non-penetrating deep sclerectomy and maximum-tolerated medical therapy for glaucoma within the Brazilian National Health System (SUS) - Guedes,Ricardo Augusto Paletta (2012)
PURPOSE: Non-penetrating deep sclerectomy (NPDS) has emerged as a viable option in the surgical management of open-angle glaucoma. Our aim is to assess the cost-effectiveness of NPDS and to compare it to maximum medical treatment in a 5-year follow-up. METHODS: A decision analysis model was built. Surgical (NPDS) arm of the decision tree was observational (consecutive retrospective case series) and maximum medical treatment arm was hypothetical. Maximum medical therapy was considered a three-drug regimen (association of a fixed combination of timolol/dorzolamide [FCTD] and a prostaglandin analogue [bimatoprost, latanoprost or travoprost]). Cost-effectiveness ratio was defined as direct cost (US dollars) for each percentage of intraocular pressure (IOP) reduction. Horizon was 5 years and perspective is from the public health care service in Brazil (SUS). Incremental cost-effectiveness ratio (ICER) was calculated. RESULTS: Direct cost for each percentage of IOP reduction in 5 years (cost-effectiveness ratio) was US$ 10.19 for NPDS; US$ 37.45 for the association of a FCTD and bimatoprost; US$ 39.33 for FCTD and travoprost; and US$ 41.42 for FCTD and latanoprost. NPDS demonstrated a better cost-effectiveness ratio, compared to maximum medical therapy. The ICER was negative for all medical treatment options; therefore NPDS was dominant. CONCLUSIONS: Despite some limitations, NPDS was both less costly and more effective than maximum medical therapy. From the Brazilian public health perspective, it was the most cost-effective treatment option when compared to maximum medical therapy (FCTD and prostaglandin).